Global prevalence of latent toxoplasmosis in pregnant women: a systematic review and meta-analysis. (June 2020) - Rostami, A.; Riahi, S.M.; Gamble, H.R.; Fakhri, Y.; Nourollahpour Shiadeh, M.; Danesh, M.; Behniafar, H.; Paktinat, S.; Foroutan, M.; Mokdad, A.H.; Hotez, P.J.; Gasser, R.B.
Abstract: Background: Toxoplasma gondii infection, if acquired as an acute infection during pregnancy, can have substantial adverse effects on mothers, fetuses and newborns. Latent toxoplasmosis also causes a variety of pathologies and has been linked to adverse effects on pregnancy. Objective: Here, we present results of a comprehensive systematic review and meta-analysis of the global prevalence of latent toxoplasmosis in pregnant women. Data source: We searched PubMed, EMBASE, Web of Science, SciELO and Scopus databases for relevant studies that were published between 1 January 1988 and 20 July 2019. Study eligibility criteria: All population-based, cross-sectional and longitudinal studies reporting the prevalence of latent toxoplasmosis in healthy pregnant women were considered for inclusion. Participants: Pregnant women who were tested for prevalence of latent toxoplasmosis. Interventions: There were no interventions. Method: We used a random effects model to calculate pooled prevalence estimates with 95% confidence intervals (CIs). We grouped prevalence data according to the geographic regions defined by the World Health Organization (WHO). Multiple subgroup and meta-regression analyses were performed. Results: In total, 311 studies with 320 relevant data sets representing 1 148 677 pregnant women from 91 countries were eligible for inclusion in the meta-analysis. The global prevalence of latent toxoplasmosis in pregnant women was estimated at 33.8% (95% CI, 31.8–35.9%; 345 870/1 148 677). South America had the highest pooled prevalence (56.2%; 50.5–62.8%) of latent toxoplasmosis in pregnant women, whereas the Western Pacific region had the lowest prevalence (11.8%; 8.1–16.0%). A significantly higher prevalence of latent toxoplasmosis was associated with countries with low income and low human development indices (p < 0.001). Conclusion: Our results indicate a high level of latent toxoplasmosis in pregnant women, especially in some low- and middle-income countries of Africa and South America, although the local prevalence varied markedly. These results suggest a need for improved prevention and control efforts to reduce the health risks to women and newborns.